The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1192/bjo.2022.70
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and mixed-methods synthesis of the experiences, perceptions and attitudes of prison staff regarding adult prisoners who self-harm

Abstract: Background Self-harm, including suicide, is common among prisoners. Staff attitudes and perceptions regarding self-harm may affect quality of care and patient safety. Aims To systematically review the experiences, perceptions and attitudes of staff in adult prisons regarding self-harm. Method Systematic searches of EMBASE, Medline, PsycINFO and CINAHL databases were conducted, and supplemented by hand-searching and grey literature review, to identify relevant English-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…After conducting a meta‐analysis of the risk factors for self‐harm in prison, Favril et al (2020: 688–689) conclude both individual and environmental factors influence this behaviour, such that “prisoners might import a vulnerability for self‐harm into prison […] that might interact with custody‐specific stressors […] and thereby increase the likelihood of self‐harming”. Indeed, studies indicate that staff‐prisoner relationships, staff perceptions, attitudes and knowledge about self‐harm, as well as the availability of services and training can influence the quality of care received and amount of distressed experienced (Ekanem & Woods, 2022; Hewson et al, 2022). Consequently, while people may import risk factors for self‐harm into prison, the nature of imprisonment and limitations in the ability of prisons to cope with this behaviour may significantly worsen this behaviour and the psychological distress experienced.…”
Section: Introductionmentioning
confidence: 99%
“…After conducting a meta‐analysis of the risk factors for self‐harm in prison, Favril et al (2020: 688–689) conclude both individual and environmental factors influence this behaviour, such that “prisoners might import a vulnerability for self‐harm into prison […] that might interact with custody‐specific stressors […] and thereby increase the likelihood of self‐harming”. Indeed, studies indicate that staff‐prisoner relationships, staff perceptions, attitudes and knowledge about self‐harm, as well as the availability of services and training can influence the quality of care received and amount of distressed experienced (Ekanem & Woods, 2022; Hewson et al, 2022). Consequently, while people may import risk factors for self‐harm into prison, the nature of imprisonment and limitations in the ability of prisons to cope with this behaviour may significantly worsen this behaviour and the psychological distress experienced.…”
Section: Introductionmentioning
confidence: 99%
“…Recent work reviewing the available evidence has suggested that prison regime characteristics, namely time out of cell and time in purposeful activity, may influence self-harm and suicide risk in prisons 7 . In addition, qualitative and cross-sectional research implicates a broader range of prison environmental factors potentially implicated in self-harm such as staffing levels, relationships between prisoners and staff, staff turnover, prisoner turnover and overcrowding [8][9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%
“…Half of prisoners who die by suicide in prison have a history of self-harm, which is associated with between six- and eleven-times increased odds of suicide [ 11 ]. A recent systematic review and mixed-methods synthesis found that prison officers often underestimate the association between self-harm and suicide [ 12 ], even though prior self-harm consistently predicts subsequent suicide in prison or after release [ 13 ]. Prison staff have been found instead to characterise self-harm as being manipulative or attention seeking, and to perceive institutional guidance on the appropriate responses to self-harm as being ambiguous [ 14 ].…”
Section: Introductionmentioning
confidence: 99%